A study with Paperless Electronic Medical Advice - Hu Sheng Li; Chi Jin Qing (MATEC Web of Conferences, 2016)
The purpose of this study is to drive the EMR’s further application and rapid expansion clinically based on the electronic medical advice as the core thereby realizing the paperless EMR. This paper has analyzed the implementation effects of electronic medical advice, followed by discussion of frequently asked questions (FAQ) and development direction, and finally analyzed the solution of paperless EMR. It indicates that electronic signatures and unitrust time stamp are keys to achieve the paperless EMR. The laws and regulations, new ideas, paperless consultation sheets, all data integration and sharing, virtual printing technology, application of wireless and mobile ward-round trolley, etc. within the health care field shall be proposed to be improved. It is significantly important to save the medical costs, reduce the medical negligence, achieve the paperless EMR and build a high-quality digital hospital.